2020
DOI: 10.1101/2020.09.27.315846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endosomal Sorting Drives the Formation of Mutant Prion Endoggresomes

Abstract: Intra-axonal misfolded protein aggregates are a pathological feature of neurodegenerative diseases. How aggregates are formed and cleared is key to maintaining proteostasis. By systematically analyzing the trafficking itinerary of a misfolded GPI-anchored prion protein (PrP) mutant, we unveil endocytic pathways that drive its immediate degradation in the soma, versus its aggregation in axons inside endosomal structures we termed endoggresomes. Axonal sorting occurs post-Golgi, by association of mutant PrP vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…These authors suggested that, when paired with cognitive data, these neurite enlargements seen with AD brains suggest a compensatory increase in size to maintain equivalent synaptic transmission rates despite a significant loss in the number of synaptic contacts (Bertoni-Freddari et al, 1993;Scheff et al, 1990). A second observation, that has also been reported in AD patients, suggests that abnormal neurite swelling likely occurs because of aberrant accumulation of axonal cargo and cytoskeletal proteins (Argueti-Ostrovsky et al, 2021;Chassefeyre et al, 2021;Stokin et al, 2005) driven by defects in axonal transport and autophagic clearance mechanisms (Argueti-Ostrovsky et al, 2021;Kobro-Flatmoen et al, 2021). Given the association between metabolic dysregulation and intracellular impairments such as cellular transport and autophagy, it is likely that the neurite enlargements observed both by us and with previous AD reports implicate a strong metabolic component in the progression of cognitive decline.…”
Section: Insulin Resistance Alters Neuron Morphology and Synaptic Pro...mentioning
confidence: 93%
See 1 more Smart Citation
“…These authors suggested that, when paired with cognitive data, these neurite enlargements seen with AD brains suggest a compensatory increase in size to maintain equivalent synaptic transmission rates despite a significant loss in the number of synaptic contacts (Bertoni-Freddari et al, 1993;Scheff et al, 1990). A second observation, that has also been reported in AD patients, suggests that abnormal neurite swelling likely occurs because of aberrant accumulation of axonal cargo and cytoskeletal proteins (Argueti-Ostrovsky et al, 2021;Chassefeyre et al, 2021;Stokin et al, 2005) driven by defects in axonal transport and autophagic clearance mechanisms (Argueti-Ostrovsky et al, 2021;Kobro-Flatmoen et al, 2021). Given the association between metabolic dysregulation and intracellular impairments such as cellular transport and autophagy, it is likely that the neurite enlargements observed both by us and with previous AD reports implicate a strong metabolic component in the progression of cognitive decline.…”
Section: Insulin Resistance Alters Neuron Morphology and Synaptic Pro...mentioning
confidence: 93%
“…Given the known off-target effects of MET, it is not unusual for differences in outcomes to be observed when comparing results between types of AMPK activators (MET vs. A-769662 (Yang et al, 2022) vs. AICAR (Amato et al, 2011)). However, one explanation for these differences may be that METinduced enlargements in neurite size and length are a response to cellular stress and reductions in synaptic protein content similar to those observed with IR treatments (Argueti-Ostrovsky et al, 2021;Chassefeyre et al, 2021;Stokin et al, 2005). This would be despite MET and IR clearly inducing the activation of separate pathways where the underlying driver might be related to a perturbed metabolic state.…”
Section: Ampk Activation On Synapse Regulationmentioning
confidence: 99%